La financiarización de los hogares bajo el prisma de otras crisis = The financialization of households observed through the prism of other crisis - Luzzi, Mariana (Civitas - Revista de Ciências Sociais, 2017)
Based on research on conflicts produced with respect to mortgage debt in dollars during the Argentine crisis of 2001, this article intends to contribute to the reflection on the importance that Finance has acquired for households during the last decades. We assert that these conflicts are indicative of the ways in which the extension of financiarisation was produced in Argentina, during a period of neoliberal reforms, and of its impact on families’ economic lives. First, we show the modalities and variable rhythms that the process of financialization took on in national contexts that are not always considered in the existing literature on financialization generally focused exclusively on the experience of developed countries. Second, we address one of the most important effects of that process: the formation of collectives (here, mortgage debtors) produced in interaction with such development of finance. The type of social composition, demands and interaction with the public authorities sustained by these groups are a central part of the analysis developed in this work